Cholera outbreak in Syria amid humanitarian crisis: the epidemic threat, future health implications, and response strategy – a review - Eneh, Stanley Chinedu; Admad, Sofya; Nazir, Abubakar; Onukansi, Francisca Ogochukwu; Oluwatobi, Alese; Innocent, David Chinaecherem; Ojo, Temitope Olumuyiwa (Frontiers in Public Health, 2023)
The war in Syria, which started over 11 years ago, has devastated the country’s water sources, healthcare system, and other vital facilities for healthy living. The country is vulnerable to outbreaks, especially epidemic-prone ones like cholera, due to its fragile health system. Syria experienced its last hit of cholera in 2009, which led to the deaths of several Syrian children and affected about 1,000 people. The current cholera resurgence in Syria calls for public concern. Considering the poor access to clean water, the forced relocation of people, and other destruction caused by the war, these factors have exposed Syrian children to infectious diseases like cholera. We argued for more efforts toward the implementation of WASH in the country. We also pointed out the need for proper education and sensitization campaigns using all available resources to educate the populace, mass chlorination of wells, mapping vulnerable areas, and implementing WASH while encouraging vaccination coverage for cholera as a strategy to reduce its incidence. Improving the national surveillance systems will aid in the timely and appropriate reporting of any outbreak. Again, more negotiations should be done to seek a lasting solution to ending the war and restoring peace and serenity in the country.